" The Teacher's Competencies In Observing Individual Differences Between pupils" A Research From The Point Of View Of Educational Mentors In Latakia City (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aimed to identify the competencies of teachers in observing the individual differences between pupils as determined by Educative Mentors, and whether these competences differ between teachers according to their educational qualification, administrative-work experience, and participation in trainings. In order to achieve the research's objectives; the researcher prepared a questionnaire addressed to the educative mentors in the schools of Lattakia city. It consists of (17) phrases covering the following fields (pupils, planning and implementation, and evaluation). The questionnaire was applied to a random sample of (21) mentors taking into account the educational qualification, participation in trainings, and administrative-work experience.The results of the research showed that, from the perspective of mentors, it is crucial teachers to have competences about pupils firstly, followed by planning and implementation competences, then evaluation competence. While in reality, teachers' competences are evaluation, planning, implementation, and students related competences respectively. Also, it showed that there is no difference between mentors’ perspectives according to their educational qualification or participation in trainings. On the other hand, there is difference between their perspectives based on administrative work- experience; in favor of experience less than 5 years.